Case report and literature review: Novel compound heterozygous FIG4 variants causing both of peripheral and central nervous system defects - Yu, Yonglin; Yin, Hongwei; Ma, Changli; Jia, Xiaoyi; Chen, Wencong; Li, Haifeng; Wu, Ke (Frontiers in Pediatrics, 2022)
Background: Pathogenic variants in the FIG4 gene have been described to be associated with a diverse spectrum of syndromes, such as autosomal recessive bilateral temporooccipital polymicrogyria (OMIM 612691), autosomal dominant amyotrophic lateral sclerosis-11 (ALS11; OMIM 612577), autosomal recessive Charcot-Marie-Tooth disease, type 4J (CMT4J; OMIM 611228), and autosomal recessive Yunis-Varon syndrome (YVS; OMIM 216340). Heterozygous FIG4 variants are responsible for ALS11 characterized by progressive muscular weakness, atrophy, and bulbar palsy. CMT4J is a disorder of peripheral nervous system (PNS) defects mainly presenting with highly variable onset of proximal and/or distal muscle weakness. YVS is a disorder of severe neurological involvement with central nervous system (CNS) dysfunction and extensive skeletal anomalies. Case Presentation: We reported two Chinese siblings born with weakness of all limbs. They experienced rapidly progressive weakness in distal limbs. At the age of 6 years, the elder brother presented with severe scoliosis and cervical kyphosis. They both had global developmental delay and a CNS involvement with cognitive deficits and swallowing problem. Genetic screening in the patients’ family for inherited diseases was recommended. Novel compound heterozygous variants in FIG4 gene (c.2148delTinsAA and c.317A>G) were found by whole-exome sequencing (WES) in the patients. These variants were confirmed by Sanger sequencing in family members. Conclusions: Herein, we reported two Chinese male patients with CMT4J who presented with abnormal CNS features. CMT4J with CNS involvement has been very rarely reported. We hoped this study could expand the phenotypic and genetic spectrum of FIG4-related diseases. And we helped physicians to understand the genotype-phenotype correlation. Keywords: FIG4 gene; Charcot-Marie-Tooth disease; central nervous system; whole-exome sequencing; compound heterozygous variants